2015
DOI: 10.1371/journal.pone.0142307
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine-Induced Premature Chromosome Condensation Results in the Apoptosis-Like Programmed Cell Death in Root Meristems of Vicia faba

Abstract: We have demonstrated that the activation of apoptosis-like programmed cell death (AL-PCD) was a secondary result of caffeine (CF) induced premature chromosome condensation (PCC) in hydroxyurea-synchronized Vicia faba root meristem cells. Initiation of the apoptotic-like cell degradation pathway seemed to be the result of DNA damage generated by treatment with hydroxyurea (HU) [double-stranded breaks (DSBs) mostly] and co-treatment with HU/CF [single-stranded breaks (SSBs) mainly]. A single chromosome comet ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 72 publications
0
25
0
Order By: Relevance
“…Vicia faba [21]. Interestingly, Friedman and Waller [22] reported repression of mitosis and cell plate formation in coffee seeds exposed to 10 mM caffeine, while Valster and Hepler [23] observed that caffeine allows initiation of the cell plate formation but prevents its completion in living Tradescantia stamen hair cells.…”
Section: Premature Chromosome Condensation Resulting In Apoptosis-likmentioning
confidence: 99%
“…Vicia faba [21]. Interestingly, Friedman and Waller [22] reported repression of mitosis and cell plate formation in coffee seeds exposed to 10 mM caffeine, while Valster and Hepler [23] observed that caffeine allows initiation of the cell plate formation but prevents its completion in living Tradescantia stamen hair cells.…”
Section: Premature Chromosome Condensation Resulting In Apoptosis-likmentioning
confidence: 99%
“…Programmed cell death (PCD) is an important physiological process in single cells and penetrates the whole plant life cycle, which can help plants to control and organize the destruction of non-functional or redundant damaged cells [ 13 , 14 , 15 ]. Although PCD is a natural result of ageing, it may be switched on by environmental stress or irregular development in plants [ 15 ]. Increases in caspase-like proteases [ 16 ] and ROS [ 17 , 18 ] activities of metacaspase gene family related genes [ 19 ] are the important features of PCD.…”
Section: Discussionmentioning
confidence: 99%
“…The apoptosis was first observed in the epidermal cells and later in the cotyledons and hypocotyls [28]. The results obtained under transmission electron microscopy (TEM) further revealed apoptotic-like features at the ultrastructural level of PCD-type cells: extensive vacuolization, abnormal chromatin condensation, its marginalization and concomitant degradation, formation of autophagylike vesicles, protoplast shrinkage, fragmentation of cell nuclei, and extensive degeneration of the cells [29]. Wang found that heat stress induced PCD in maize seedling leaves, which was characterized by chromatin DNA laddering and DNA strand breaks detected by a terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) test [30].…”
Section: Discussionmentioning
confidence: 99%
“…DAPI staining was performed according to [7]. Terminal bud DNA was extracted by the CTAB method [8].…”
Section: Test Methodsmentioning
confidence: 99%